2019
DOI: 10.1080/15384101.2019.1642065
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 affects the progress of G2/M by regulating Aurora-A

Abstract: Aurora-A is a serine/threonine kinase, which is overexpressed in multiple human cancers and plays a key role in tumorigenesis and tumor development. In this study, we found that the receptor of activated C-kinase1 (RACK1), an important regulator of biological functions, interacted with Aurora-A and co-localized with Aurora-A at centrosomes. Moreover, RACK1 induces the autophosphorylation of Aurora-A in vitro and in vivo. Depletion of RACK1 impaired the activation of Aurora-A in late G2 phase, then inhibited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Previous studies have demonstrated the critical roles of RACK1 in regulating the processes of cancer cell proliferation, adhesion, migration, invasion and metastasis (45)(46)(47)(48)(49). RACK1, ubiquitously expressed in a wide range of tissues, was initially identified as an anchoring protein for protein kinase C (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the critical roles of RACK1 in regulating the processes of cancer cell proliferation, adhesion, migration, invasion and metastasis (45)(46)(47)(48)(49). RACK1, ubiquitously expressed in a wide range of tissues, was initially identified as an anchoring protein for protein kinase C (55).…”
Section: Discussionmentioning
confidence: 99%
“…RACK1, which contains seven Trp-Asp 40 (WD40) repeats, is a scaffold protein with diverse functions that has been reported to interact with several receptors and regulate signaling pathways (45)(46)(47)(48)(49). To determine the functional significance of the association between CCDC102B and RACK1, we examined the expression level of RACK1 (Supplementary Figure 4B).…”
Section: Rack1 Decreases the Stability Of Ccdc102b Through The Lysoso...mentioning
confidence: 99%
“…However, how Aurora-A is activated is not fully understood. Some activators of Aurora-A are known, including the LIM-domain protein Ajuba ( Goyal et al, 1999 ; Hirota et al, 2003 ), the microtubule-associated protein TPX2 ( Eyers et al, 2003 ), p21-activated protein kinase 1 (Pak1) ( Zhao et al, 2005 ), thyroid hormone receptor-associated protein complex component/methyl-CpG binding endonuclease TRAP220/MED1 ( Udayakumar et al, 2006 ), EGFR ( Hung et al, 2008 ; Lai et al, 2010 ), ubiquitin-specific processing protease-7 (USP7) ( Giovinazzi et al, 2013 ), a classic tumor suppressor p53 ( Yang et al, 2018 ), heterogeneous nuclear ribonucleoprotein Q1 protein (HnRNP Q1) ( Lai et al, 2018 ), the receptor of activated C-kinase1 (RACK1) ( Shen et al, 2019 ), the NE proteins containing the LEM domain LEM4 ( Gao et al, 2018 ), and KIAA1529 ( Qiao et al, 2022 ). Most notably, EGF can increase Aurora-A gene expression through the nuclear EGFR/STAT5 signaling pathway and ultimately lead to chromosome instability and tumorigenesis ( Hung et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The AURK family, consisting of AURKA, AURKB and AURKC in mammals, is a group of serine/threonine kinase enzymes. These mitotic kinases promote cell proliferation through involvement in the G2/M stage of the cell cycle [7,8]. Among these, AURKA and AURKB play important roles in the regulation of mitosis, whereas AURKC is speci cally expressed in mammalian testis.…”
Section: Introductionmentioning
confidence: 99%